Clinical Value of Low-Dose Spiral CT Combined with Serum CEA in the Differential Diagnosis of Early Lung Cancer - Jin J; Wu L (Cancer Management and Research, 2025)
Jianguo Jin,1 Liping Wu2 1Department of Radiology, First People’s Hospital of Linping District, Hangzhou, Zhejiang, People’s Republic of China; 2Department of General Geriatrics, Integrated Traditional Chinese, Hangzhou of Linping District, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Liping Wu, Department of General Geriatrics, Integrated Traditional Chinese, Hangzhou of Linping District, No. 369 of Yingbin Road, Nanyuan Street, Linping District, Hangzhou, Zhejiang, 311100, People’s Republic of China, Tel +86– 18072889033, Email 13376819518@163.comPurpose: Early detection of lung cancer is critical to improving prognosis, yet current screening methods such as low-dose spiral CT and serum CEA each have diagnostic limitations. This study aims to analyze the clinical value of low-dose spiral CT combined with serum CEA in the differential diagnosis of early lung cancer.Materials and Methods: In this retrospective study, 62 patients diagnosed with early lung cancer in our hospital from April 2022 to October 2023 were selected as the case group, and 50 patients diagnosed with benign pulmonary lesions during the same period were selected as the control group. Data from low-dose spiral CT and serum CEA levels were compared. The efficacy of low-dose spiral CT alone, serum CEA alone, and the combination of both in discriminating early lung cancer was assessed using ROC curves.Results: Low-dose spiral CT showed a sensitivity of 77.42%, a specificity of 94.00%, and an AUC of 0.8571 (95% CI: 0.7832– 0.9310) in detecting early lung cancer. Serum CEA levels were significantly higher in the case group compared to the control group (P< 0.05). Serum CEA yielded an AUC of 0.8661 (95% CI: 0.7964– 0.9359) in distinguishing early lung cancer (P< 0.0001). Low-dose spiral CT combined with serum CEA detection achieved an AUC of 0.9137 (95% CI: 0.8624– 0.9650), significantly increasing the early lung cancer detection rate from 82.26% to 95.16% (P< 0.05).Conclusion: Patients with early lung cancer show distinct alterations in low-dose spiral CT signs, and their serum CEA levels demonstrate a notable increase compared with those with benign pulmonary lesions. The combination of low-dose spiral CT with serum CEA can be considered in the discrimination of early lung cancer, which can markedly enhance the positive detection rate while maintaining a minimal rise in false-positive rates.Keywords: low-dose spiral CT, serum carcinoembryonic antigen, early lung cancer, combined detection, discriminative value